PENGARUH DIET TERHADAP PENURUNAN KADAR GLUKOSA DARAH SEWAKTU PADA PASIEN DIABETES MELLITUS TIPE 2 DI WILAYAH PUSKESMAS SUSUKAN BANJARNEGARA - Imam Setiyo Aji; Sudiarto; Fida Dyah Puspitasari (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2023)
Diabetes has become a deadly disease considering the many risks of complications that can attack the body such as the eyes, kidneys, nerves, to the heart and the possibility of amputation. In Central Java, the prevalence of people with diabetes mellitus is around 2.1% or 67,977 people suffer from diabetes mellitus. Type 2 DM is a disease characterized by hyperglycemia with complaints of polyphagia, polydipsia, polyuria. To keep blood glucose levels stable, patients with type 2 DM are advised to have a proper diet with 3J (jumlah, jam, jenis makanan). To determine the effect of diet on blood glucose during type 2 DM patients. The writing of this KTI uses the case study method with respondents who have type 2 DM in the Susukan Health Center area. The results of the case study found that diet can have an effect on decreasing blood glucose levels during. There is a temporary decrease in blood glucose levels in patients with type 2 DM after undergoing a diet 3J for 7 days with a blood glucose level of 85 mg/dl.